2016
DOI: 10.1097/ijg.0000000000000284
|View full text |Cite
|
Sign up to set email alerts
|

Novel Parameter of Corneal Biomechanics That Differentiate Normals From Glaucoma

Abstract: Glaucomatous eyes have a greater mean outward applanation velocity and peak distance, but shorter time to highest concavity than eyes without glaucoma. The difference in time to highest concavity does not correlate with age, IOP, or CCT, suggesting that this parameter may be a marker of increased pressure susceptibility that is independently associated with glaucoma risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
37
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 42 publications
3
37
0
2
Order By: Relevance
“…The current study also confirmed the significant negative associations among axial length and A2T, A2V, and radius, reported by Asaoka et al 35 Lee et al 36 reported significantly larger A2V and PD values in myopic subjects, which agrees with those from the current study. 36 Together, the current study confirmed more comprehensively the results of the previous investigations that myopic eyes have less corneal deformation. Our new findings included identification of less viscous damping and less whole eye movement of myopic eyes.…”
Section: Axial Lengthsupporting
confidence: 83%
See 1 more Smart Citation
“…The current study also confirmed the significant negative associations among axial length and A2T, A2V, and radius, reported by Asaoka et al 35 Lee et al 36 reported significantly larger A2V and PD values in myopic subjects, which agrees with those from the current study. 36 Together, the current study confirmed more comprehensively the results of the previous investigations that myopic eyes have less corneal deformation. Our new findings included identification of less viscous damping and less whole eye movement of myopic eyes.…”
Section: Axial Lengthsupporting
confidence: 83%
“…This device measures a variety of parameters such as length, area, radius, arc length, and velocity of the corneal deformation at several defined time points. Previous studies have reported significant differences between the values of the corneal deformation parameters measured with the Corvis ST in normal eyes and those in eyes with glaucoma [13][14][15][16] and keratoconus 17 and after refractive 11,18,19 and keratoplasty surgeries, 20 suggesting the potential clinical relevance of the dynamic Scheimpflug analyzer to those conditions. In addition to ocular pathologies, the corneal biomechanical parameters are associated with a range of ocular and systemic factors.…”
mentioning
confidence: 99%
“…Only these adjusted parameters can be used for the interpretation of biomechanical differences [20][21][22][23][24][25][26][27]. Most of the published studies on ORA measurements do not consider these dependencies in their analysis.…”
Section: Discussionmentioning
confidence: 97%
“…16 Several articles have recently been published on the possible applications of the Corvis ST, particularly evaluating possible biomechanical differences in the cornea after undergoing refractive surgery procedures, [17][18][19][20][21][22] between normal and keratoconic patients, [23][24][25][26] after cross-linking, 27 and in patients with glaucoma. [28][29][30][31] However, it has been demonstrated that IOP and pachymetry have important influences on most corneal biomechanical metrics provided by both the Corvis ST and ORA. [32][33][34] It is therefore relevant to investigate the distribution and normal limits for the in vivo corneal biomechanical data derived from dynamic corneal response parameters, and determine whether these metrics have correlations with IOP and corneal thickness.…”
Section: Resultsmentioning
confidence: 99%